Formulasi, Evaluasi Dan Penentuan Nilai SPF Sediaan Body Lotion Ekstrak Etanol Kopi Arabika Jenis Longberry - Fanny Anggreany Santosa; Rafita Yuniarti; Minda Sari Lubis; Zulmai Rani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Exposure to ultraviolet (UV) radiation can cause skin damage such as erythema, premature aging, and skin cancer. Although sunscreens are widely used, synthetic UV filters may cause side effects. Therefore, alternative natural ingredients with antioxidant activity are needed, such as Arabica coffee beans (Coffea arabica), which are rich in polyphenols, particularly chlorogenic acid, as potential sunscreen agents. Objective: This study aims to formulate a body lotion containing ethanol extract of longberry-type Arabica coffee beans, evaluate its physical properties, and determine its Sun Protection Factor (SPF) value in vitro. Methods: This experimental study included phytochemical screening, extraction using 96% ethanol, and SPF determination using a UV-Vis spectrophotometer with the Mansur method. The body lotion was formulated with varying extract concentrations of 0–3% and evaluated for organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesiveness, emulsion type, stability, and irritation test. Results: The extract contained alkaloids, flavonoids, tannins, saponins, steroids, and glycosides. The highest SPF value of the extract was 36.727 at a concentration of 1000 ppm (ultra protection category). The best formulation was found at a 3% concentration with an SPF value of 10.554 (maximum protection category). All formulations met physical quality requirements and showed no irritation. Conclusion: The ethanol extract of longberry-type Arabica coffee beans has potential as a natural sunscreen active ingredient. Increasing the extract concentration is directly proportional to the increase in SPF value, with the 3% formulation showing the best performance.